A Balanced Approach for Cannabidiol Use in Chronic Pain - Argueta, Donovan A.; Ventura, Christopher M.; Kiven, Stacy; Sagi, Varun; Gupta, Kalpna (Frontiers in Pharmacology, 2020)
Cannabidiol (CBD), the major non-psychoactive constituent of Cannabis Sativa L., has gained traction as a potential treatment for intractable chronic pain in many conditions. Clinical evidence suggests that CBD provides therapeutic benefit in certain forms of epilepsy and imparts analgesia in certain conditions, and improves quality of life. CBD continues to be Schedule I or V on the list of controlled substances of the Drug Enforcement Agency of the United States. However, preparations labeled CBD are available publicly in stores and on the streets. However, use of CBD does not always resolve pain. CBD purchased freely entails the risk of adulteration by potentially hazardous chemicals. As well, CBD use by pregnant women is rising and poses a major health-hazard for future generations. In this mini-review, we present balanced and unbiased pre-clinical and clinical findings for the beneficial effects of CBD treatment on chronic pain and its deleterious effects on prenatal development.